Health disparities in psoriasis: geographic barriers to access in the United States - Lauren Seigel; Sofia Shoaib; Keshia Maughn; Miran Foster; Shrushti Shah; Lakshmi Batchu; Keith Wittstock; Andrew Alexis (Journal of Dermatological Treatment)
Purpose Providers who treat patients with psoriasis are unevenly distributed across the United States, with more in urban than rural areas. This retrospective claims analysis characterized disparities in access to care for US patients with psoriasis using data from the STATinMED database.Materials and methods Patients (≥18 years) had ≥1 claim with a psoriasis diagnosis and ≥1 claim for advanced psoriasis therapy (apremilast or biologics) between January 2015 and December 2019. Access to psoriasis care was determined using the proportion of patients with 0, 1–2, 3–4, or ≥5 providers in their local area.Results Overall, 179,688 patients were included in the analysis, 80.0% in urban areas. The access ratio was highest for internal medicine physicians (97.1 per 1000 patients) and lowest for dermatologists (4.4 per 1000 patients) and family practice physicians (3.9 per 1000 patients). In urban areas, 41% of patients had access to ≥5 dermatologists versus 7% in rural areas. Whereas 2% of patients in urban areas sought care outside of their local area, 75% in rural areas did so. Use of advanced therapies was low in all states (<17%).Conclusion Access to psoriasis-treating providers varied widely. Regardless of access, utilization of advanced treatments was low, suggesting the need for effective, easy-to-administer therapy.